Environmental Conditions Associated with Four Index Cases of Pacific Oyster Mortality Syndrome (POMS) in Crassostrea gigas in Australia Between 2010 and 2024: Emergence or Introduction of Ostreid herpesvirus-1? - Richard J. Whittington; Lachlan Ingram; Ana Rubio (Animals)
Warm water temperature is a risk factor for recurrent mass mortality in farmed Pacific oysters Crassostrea gigas caused by Ostreid herpesvirus-1, but there is little information on environmental conditions when the disease first appears in a region—the index case. Environmental conditions between four index cases in Australia (2010, 2013, 2016 and 2024) were compared to provide insight into possible origins of the virus. Each index case was preceded by unusually low rainfall and higher rates of temperature change that could increase oyster susceptibility through thermal flux stress. Water temperature alone did not explain the index cases, there being no consistency in sea surface, estuary or air temperatures between them. Tidal cycles and chlorophyll-a levels were unremarkable, harmful algae were present in all index cases and anthropogenic environmental contamination was unlikely. The lack of an interpretable change in the estuarine environment suggests the recent introduction of OsHV-1; however, viral emergence from a local reservoir cannot be excluded. Future events will be difficult to predict. Temperature flux and rainfall are likely important, but they are proxies for a range of undetermined factors and to identify these, it will be necessary to develop comprehensive protocols for data acquisition during future index cases.